Design of a novel high efficiency antenna for helicon plasma sources. (17th May 2018) - Fazelpour, S.; Chakhmachi, A.; Iraji, D.; Sadeghi, H.
Abstract : A new configuration for an antenna, which increases the absorption power and plasma density, is proposed for helicon plasma sources. The influence of the electromagnetic wave pattern symmetry on the plasma density and absorption power in a helicon plasma source with a common antenna (Nagoya) is analysed by using the standard COMSOL Multiphysics 5.3 software. In contrast to the theoretical model prediction, the electromagnetic wave does not represent a symmetric pattern for the common Nagoya antenna. In this work, a new configuration for an antenna is proposed which refines the asymmetries of the wave pattern in helicon plasma sources. The plasma parameters such as plasma density and absorption rate for a common Nagoya antenna and our proposed antenna under the same conditions are studied using simulations. In addition, the plasma density of seven operational helicon plasma source devices, having a common Nagoya antenna, is compared with the simulation results of our proposed antenna and the common Nagoya antenna. The simulation results show that the density of the plasma, which is produced by using our proposed antenna, is approximately twice in comparison to the plasma density produced by using the common Nagoya antenna. In fact, the simulation results indicate that the electric and magnetic fields symmetry of the helicon wave plays a vital role in increasing wave–particle coupling. As a result, wave–particle energy exchange and the plasma density of helicon plasma sources will be increased.